Madrasah Tsanawiyah Student Smartphone Behavior and Parental Characteristics in Relationship to Smartphone Overuse - Saidah Rauf; Nunung Dwi Setyawati (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
Smartphone use has exploded in recent decades. It has become more noticeable in education, inextricably linked to the Covid-19 pandemic, particularly adolescent students. This study aimed to estimate the Madrasah Tsanawiyah students’ smartphone use behavior, application type usage, and its relationship with gender and parental factors. This was a cross-sectional study conducted using online survey research. The current study was carried out at Maluku Tengah's Madrasah Tsanawiyah Negeri 2 (MTSN 2). The sample consisted of 130 students from all grades. This study demonstrated that participants use their smartphones quite frequently. More than half of the participants (54.6%) used their smartphone ≥20 hours per week, outside of regular online learning hours. The participant risks factors of smartphone overuse were social media apps used for females (OR=3.93) and online game apps for males (OR=6.71). Based on parental characteristics, fathers’ age ≥45 years and non-housewife mothers were a risk factor for smartphone overuse in students (OR=2.34 and OR=9.22).